(untitled) (TRAKIA JOURNAL OF SCIENCES, 2025)
This article examines specific factors that influence the participation of health care professionals in continuing education. The study is based on a review of accessible literature, including scientific publications, doctoral dissertations, strategic reports, and institutional documents discussing the individual, organizational, and societal determinants that shape the engagement of medical specialists in qualification programs. The selected sources were analysed through qualitative synthesis and content interpretation, focusing on current trends, good practices, and challenges reflected in national and international contexts. The findings reveal that motivation, organizational support, and access to resources are among the key factors that define active participation in continuing education. Innovative approaches and models—such as e-learning, mentoring programs, and flexible forms of qualification—are presented as effective means of facilitating participation and improving the quality and safety of health services. In conclusion, the study emphasizes the need for sustainable strategies and policies for human resource development in health care through systematic and accessible continuing education initiatives.